Enhancing Reading Comprehension in Fourth Graders: Evaluating the Impact of the Cooperative Integrated Reading Composition (CIRC) Model - Zelsa Pratami Putri; Neni Hermita; Eva Astuti Mulyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on the reading comprehension skills of elementary school students. A quantitative, pre-experimental research design was employed, specifically the One-Group Pretest–Posttest Design. A group of fourth-grade students was administered a pretest to assess their baseline reading comprehension. Following this, they received instruction using the CIRC model. After the intervention, a posttest was conducted to measure any changes in performance. The data were analyzed using paired sample t-tests and normalized gain (N-Gain) scores to determine both statistical significance and instructional effectiveness. The t-test yielded a significance value of 0.000 (p 0.05), indicating a statistically significant improvement in reading comprehension after the application of the CIRC model. The students' average score increased markedly from 45.63 on the pretest to 76.68 on the posttest. Additionally, the N-Gain score was 74.34%, placing the model in the "effective" category for improving comprehension. The findings demonstrate that the CIRC model significantly enhances the reading comprehension skills of fourth-grade elementary students. The increase in test scores and high N-Gain percentage support the use of CIRC as an effective instructional strategy in primary education.